Study into the Feasibility of Basic Modernization of a Copper Smelter using the Roasting-Smelting Flow Diagram for Treatment of Sulphide Feed Materials - A. V. Tarasov (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
There are still a number of copper smelters in the world using the roasting and smelting process flow diagram for treating sulphide raw materials. The technical, economic and environmental performance indicators of such operations are inferior to the respective indicators of advanced processes. First of all with respect to copper and sulphur recovery: 95% and 75% as compared with 98% and over 90%, respectively. Based on the studies of the single-stage smelting process to produce white metal and blister copper conducted during recent years an analysis of the feasibility of roastingsmelting technology improvement was carried out in the Gintsvetmet Institute to substantially increase the copper and sulphur recoveries. On the basis of this analysis, it was proposed to modernize the technology and equipment within the framework of the existing process flow-sheet. The proposed modernization implies an increase in the roasting temperature; higher desulphurization degree in the process of roasting; a number of modifications in the roaster design depending on the particular conditions of a given operation; addition of lime flux to the feed charge to roasting; and transition to combined calcium-silicate smelting slags. The metallurgical and energy computations made have indicated that the proposed modifications of the technology will improve the copper and sulphur recovery up to 98% and 90%, respectively. The required capital investments have been estimated using as an example a particular copper smelter, the payback period determined taking into consideration additional output, fuel saving and a reduction in fines for sulphur emissions. For comparison, the capital cost of a smelter modernization is given for change-over to basically new autogenous Ausmelt, Outokumpu and V anyukov smelting technologies.